Mastering HTML5 game development - Albu, Daniel; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2016)
"HTML5 is the fifth revision of the HTML standard, which is a core technology used for structuring and presenting content on Internet. Its innovative features such as Canvas, Audio, and Video elements make it a potential game building tool. While you can use Objective-C to build games just for iOS, HTML5 gives you the ability to build games for a multitude of platforms. This is the reason game developers and designers absolutely love HTML5--it simplifies the job of creating graphically-rich interactive games for the Internet and mobile devices. This video course will help you to create interactive, dynamic, and colorful games with HTML5. We'll build a breakout game, using HTML5 Canvas to create the graphics and the main stage. We'll use CreateJS and its modular libraries to build a visually-rich game. We'll make it interactive by adding a keyboard, mouse, and touch support. Then we'll move on to set up the audio required for the game using WebAudio and HTML Audio. We'll show you how to take advantage of the SQL-like data storage facility of HTML5. Then, we'll make our game robust by carrying out its testing and debugging. Finally, we'll dive into common errors and pitfalls that developers usually commit and a way to avoid them. By the end of the course, you will be able to take full advantage of all the HTML5 features to create advanced and interactive games."--Resource description page.
Presenter, Daniel Albu.
Title from title screen (viewed August 31, 2016).
Date of publication from resource description page.
Keywords: Computer games -- Programming; HTML (Document markup language); Computer games -- Design; Video games -- Design; Video games -- Programming; Electronic books